Teachers’ Voices toward Eight National Education Standards in a Private Elementary School in Yogyakarta - Sibakhul Milad Malik Hidayatulloh; Berliana Dyah Ayu Aprilianti (Jurnal Siliwangi: Seri Pendidikan, 2021)
To make Indonesia’s education system equal to each other, Indonesia through the Ministry of Education and Culture has already set the eight national education standards. This research aims to explore the implementation of the eight education standards in one of private elementary schools in Yogyakarta. The participants of this research are four teachers from the reference school. Moreover, those participants also have a functional position in that school such as headmaster, treasurer, and curriculum designer. A descriptive qualitative will be used in this research to find out the research’s result. The research questions for this research are: 1) How is the implementation of eight national standards in the school, 2) What are the teachers’ perceptions on eight national standards in a private elementary school in Yogyakarta. Using an interview guideline as the instrument, the data will be gained through in-depth interviews. From the data, it is supposed to explore the implementation of eight national education standards through teachers’ opinion in reference schools. Besides, the result will be used to evaluate the support from the government towards the implementation of eight education standards in Indonesia’s school. In addition, the limitation of this research is the choosing of elementary school because the researchers want to know the implementation started from the basis.